The Authoring Problem: Challenges in Supporting Authoring for Interactive Digital Narratives - Hargood, Charlie; Millard, David E; Mitchell, Alex; Spierling, Ulrike (Human–Computer Interaction Series, 2023)
Authoring, its tools, processes, and design challenges are key issues for the Interactive Digital Narrative (IDN) research community.The complexity of IDN authoring, often involving stories co-created by procedures and user interaction, creates confusion for tool developers and raises barriers for new authors.